A new shoulder model with a biologically inspired glenohumeral joint. Issue 9 (September 2016) - Quental, C.; Folgado, J.; Ambrósio, J.; Monteiro, J.
Highlights: A large-scale multibody model of the upper limb with 6 degrees of freedom for the glenohumeral joint is presented. The glenohumeral joint is modelled as a spherical joint with clearance. A novel inverse dynamics procedure is presented to estimate not only the muscle and joint reaction forces of the upper limb, but also the glenohumeral joint translations. For an abduction motion in the frontal plane, the model predicts an initial upward and posterior movement of the humeral head, followed by an inferior and anterior movement. The glenohumeral joint translations predicted are in good agreement with in-vivo, in-vitro, and computational measurements reported in the literature. Abstract: Kinematically unconstrained biomechanical models of the glenohumeral (GH) joint are needed to study the GH joint function, especially the mechanisms of joint stability. The purpose of this study is to develop a large-scale multibody model of the upper limb that simulates the 6 degrees of freedom (DOF) of the GH joint and to propose a novel inverse dynamics procedure that allows the evaluation of not only the muscle and joint reaction forces of the upper limb but also the GH joint translations. The biomechanical model developed is composed of 7 rigid bodies, constrained by 6 anatomical joints, and acted upon by 21 muscles. The GH joint is described as a spherical joint with clearance. Assuming that the GH joint translates according to the muscle load distribution, the redundant muscle load sharing problem is formulated considering as design variables the 3 translational coordinates associated with the GH joint translations, the joint reaction forces associated with the remaining kinematic constraints, and the muscle activations. For the abduction motion in the frontal plane analysed, the muscle and joint reaction forces estimated by the new biomechanical model proposed are similar to those estimated by a model in which the GH joint is modeled as an ideal spherical joint. Even though this result supports the assumption of an ideal GH joint to study the muscle load sharing problem, only a 6 DOF model of the GH joint, as the one proposed here, provides information regarding the joint translations. In this study, the biomechanical model developed predicts an initial upward and posterior migration of the humeral head, followed by an inferior and anterior movement, which is in good agreement with the literature. Graphical abstract: